South African educators’ mutually inclusive mandates to promote human rights and positive discipline - Susan Coetzee; Cathrine Mienie (Perspectives in Education, 2013)
South African educators are mandated by international and national law to observe and promote human rights. However, given the realities of the limited teaching time available, educators cannot fulfil this obligation solely by teaching the curriculum. Another avenue needs to be found for educators to fulfil this obligation. Educators are also mandated to follow a positive discipline approach, but they are still finding this mandate difficult to accept. The authors of this article contend that the mutual inclusivity of these mandates might hold the solution to both these challenges. It provides the avenue needed for educators to fulfil their human rights mandate because by implementing positive discipline, human rights are invariably observed and promoted. This is so because positive discipline is grounded in human rights. In this article the authors aim to explain the mutual inclusivity of these mandates to illustrate the fact that, by adopting a positive discipline approach, educators will be fulfilling their theoretical obligation to promote and observe human rights and will thus be making these rights a reality.